Biomaterials for Cell Delivery : Vehicles in Regenerative Medicine - Goldstein, Aaron S. (Boca Raton, FL : CRC Press, 2018)
The purpose of this book is to summarize key strategies and recent accomplishments in the area of developing cell/biomaterial constructs for regenerative medicine. The first section is a review of the state-of-the-art of biomaterial carriers and is divided into synthetic and natural materials. A subset of the latter are decellularized organs which retain the structure and some of the biological activities of the target organ. The bulk of the book is devoted to unique problems associated with key tissue and organ targets.
Chapter 8: In Vivo Cell Delivery: Pancreatic Islet TransplantationChapter 9: Cutaneous Wound Healing; Chapter 10: Incorporation of In Vitro Cell Conditioning for Enhanced Development of Tissue Engineered Skeletal Muscle Implants; Chapter 11: Conditioning Cells In Vitro to Facilitate Tendons and Ligament Regeneration; Chapter 12: In Vitro Cell Conditioning for the Development of Engineered Blood Vessels; Chapter 13: Perspectives for Clinical Translation: How Stem Cells and Biomaterials Affect Vasculogenesis and Neurogenesis in Preclinical and Clinical Models; Index
OCLC-licensed vendor bibliographic record.
Keywords: Biomedical materials; Tissue engineering; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; MEDICAL / Biotechnology; SCIENCE / Life Sciences / Cytology; TECHNOLOGY / Material Science